Physiological and self-reported arousal in virtual reality versus face-to-face emotional activation and cognitive restructuring in university students: A crossover experimental study using wearable monitoring. (July 2021) - Bolinski, Felix; Etzelmüller, Anne; De Witte, Nele A.J.; van Beurden, Cecile; Debard, Glen; Bonroy, Bert; Cuijpers, Pim; Riper, Heleen; Kleiboer, Annet
Abstract: Background: Arousal may be important for learning to restructure ones' negative cognitions, a core technique in depression treatment. In virtual reality (VR), situations may be experienced more vividly than, e.g., in an imaginative approach, potentially aiding the emotional activation of negative cognitions. However, it is unclear whether such activation and subsequent cognitive restructuring in VR elicits more physiological, e.g. changes in skin conductance (SC), heart rate (HR), and self-reported arousal. Method: In a cross-over experiment, 41 healthy students experienced two sets, one in VR, one face-to-face (F2F), of three situations aimed at activating negative cognitions. Order of the sets and mode of delivery were randomised. A wristband wearable monitored SC and HR; self-reported arousal was registered verbally. Results: Repeated measures analyses of variance revealed significantly more SC peaks per minute, F (1, 40) = 13.89, p = .001, higher mean SC, F (1, 40) = 7.47, p = .001, and higher mean HR, F (1, 40) = 75.84, p < .001 in VR compared to F2F. No differences emerged on the paired-samples t -test for self-reported arousal, t (40) = −1.35, p = .18. Discussion: To the best of our knowledge, this is the first study indicating that emotional activation and subsequent cognitive restructuring in VR can lead to significantly more physiological arousal compared to an imaginative approach. These findings need to be replicated before they can be extended to patient populations. Highlights: A crossover experiment was conducted on 41 healthy university students. They used emotional activation and cognitive restructuring techniques in VR and face-to-face (F2F). Physiological arousal was higher in the VR than the F2F component ( p ≤ .001). Skin conductance increased from VR tutorial to VR intervention ( p ≤ .001). No difference between VR and F2F was found on self-reported arousal ( p = .18).